2023
DOI: 10.1021/acsorginorgau.3c00008
|View full text |Cite
|
Sign up to set email alerts
|

On the Redox Properties of the Dimers of Thiazol-2-ylidenes That Are Relevant for Radical Catalysis

Abstract: We report the isolation and study of dimers stemming from popular thiazol-2ylidene organocatalysts. The model featuring 2,6-di(isopropyl)phenyl (Dipp) N-substituents was found to be a stronger reducing agent (E ox = −0.8 V vs SCE) than bis(thiazol-2-ylidenes) previously studied in the literature. In addition, a remarkable potential gap between the first and second oxidation of the dimer also allows for the isolation of the corresponding airpersistent radical cation. The latter is an unexpected efficient promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Attempts at compound 2a metallation using PdCl 2 , 54 PdPy 2 Cl 2 , 6 NiCp 2 , 55 Cu 2 O 56 and Ag 2 O 57 in previously described conditions were unsuccessful, and only complex mixtures of products were obtained. It can be proposed that this may be explained by the instability of compound 2a containing a PhSO 2 group, which may suffer desulfonylation reactions, 58–61 as well as, possibly, other redox reactions with in situ generated NHCs (potential reducing agents) 62–68 under the reaction conditions. For example, complex 4a containing an NHC ligand without a PhSO 2 group was isolated in low yield (7%) after palladation of 2a with PdPy 2 Cl 2 in dioxane in the presence of K 2 CO 3 (Scheme 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts at compound 2a metallation using PdCl 2 , 54 PdPy 2 Cl 2 , 6 NiCp 2 , 55 Cu 2 O 56 and Ag 2 O 57 in previously described conditions were unsuccessful, and only complex mixtures of products were obtained. It can be proposed that this may be explained by the instability of compound 2a containing a PhSO 2 group, which may suffer desulfonylation reactions, 58–61 as well as, possibly, other redox reactions with in situ generated NHCs (potential reducing agents) 62–68 under the reaction conditions. For example, complex 4a containing an NHC ligand without a PhSO 2 group was isolated in low yield (7%) after palladation of 2a with PdPy 2 Cl 2 in dioxane in the presence of K 2 CO 3 (Scheme 3a).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, thiazol-2-ylidenes have been postulated as single-electron donors in their own rights, and therefore as rare examples of organic reductants. However, a recent report by Martin, Tomás-Mendivil et al showed that during the reaction, the thiazol-2-ylidenes dimerize leading to the corresponding electron-rich olefins, a class of compounds which have already been demonstrated as potent organic reductants . Regardless of this issue, the question remains whether a stable singlet carbene could act as an organic reducing agent.…”
mentioning
confidence: 99%
“…To avoid the issue discussed above for thiazol-2-ylidenes, we chose to use 1 H -1,2,3-triazol-5-ylidenes A , since mesoionic carbenes do not dimerize. We report the use of carbene A as both stoichiometric and catalytic organic reductants.…”
mentioning
confidence: 99%
“…Electron-rich olefins stemming from the dimerization of thiazolylidenes often feature a variety of geometrical distortions around the C=C double bond. 2a 11b 19 Dimer 5e provided another example of an unusual topology. Indeed, the X-ray diffraction study revealed a nonplanar structure of the E -isomer with syn out-of-plane bending and pronounced pyramidalization at the nitrogen atoms.…”
mentioning
confidence: 99%
“…In marked contrast, the dimer 5h , stemming from 3h , features N -Dipp substituents that force the nitrogen atoms into a planar geometry and result in a remarkably stable radical 5h ∙+ . 11b…”
mentioning
confidence: 99%